Xenotransplantation: Fact or Magic - Mahdi, Batool Mutar (AL-Kindy College Medical Journal, 2022)
The knowledge of transferring body organs or tissues appears in the ancient mythology of Roman, Greek, Indian, Chinese, and Egyptian civilizations. The stories of organ transplants performed by GODs and health care’s using organs from cadaveric and after that transplantation change from lore to medical training